Inflation and Stock Returns at B3 - Chaves, Carlos (2019)
We examine the impact of expected inflation on stock returns. We use inflation forecasts from the Focus survey and real returns of Ibovespa (the index of B3, the Brazilian stock exchange). In our main specification, an increase of 1 percentage point in expected inflation for the next 12 months is associated with a decline of 0.57 percentage points in stock returns. Stock returns react negatively to the 5-year CDS volatility and the VIX index. A simulated portfolio with a strategy based on changes in inflation expectations from 2003 to 2016 has cumulated real returns of 135 percent while cumulated real Ibovespa returns are 48 percent. The strategy implies higher cumulated real returns compared with Ibovespa in 69 percent of the period.